Music Therapy as a Potential Intervention for Sleep Improvement - Loewy J (Dove Medical Press, 2020)
Joanne Loewy The Louis Armstrong Center for Music and Medicine, Mount Sinai Beth Israel, New York, NY 10003, USACorrespondence: Joanne LoewyThe Louis Armstrong Center for Music and Medicine, Mount Sinai Beth Israel, 10 Union Square East, New York, NY 10003, USATel +1 212 420-3484Email Joanne.Loewy@mountsinai.orgAbstract: Sleep deficiency is linked to chronic health problems, such as heart disease, kidney disease, high blood pressure, diabetes, stroke, obesity, and depression. Healthcare practitioners are increasingly paying close attention to sleep and its impact on health and wellness as a measure of critical vitality. Sleep’s impact on neurologic function, and cognitive endurance affect capacity throughout the lifespan. This article will address recent findings related to the potential of music to induce sleep in illness and wellness. Music therapy research findings and its efficacy as a potent cost-effective intervention will be highlighted.Keywords: music sedation, music therapy, sleep induction